Research in economic history, Vol. 28 (Research in economic history, 2012)
Air conditioning, migration, and climate-related wage and rent differentials / Jeff E. Biddle -- The rail-guided vehicles industry in Italy, 1861-1913 : the burden of the evidence / Carlo Ciccarelli, Stefano Fenoaltea -- English banking and payments before 1826 / John A. James -- Retail trade by Federal Reserve District, 1919 to 1939 : a statistical history / Haelim Park, Gary Richardson -- The great fortunes of the Gilded Age and the Crisis of 1893 / Hugh Rockoff